Mini clinical evaluation exercise (Mini-CEX): A tool for assessment of residents in department of surgery - Pooja Batra; Ravi Batra; Niket Verma; Pradeep Bokariya; Shreyak Garg; Sneha Yadav (Journal of Education and Health Promotion, 2022)
BACKGROUND: The mini-clinical evaluation exercise (mini-CEX) is a formative assessment tool designed to provide feedback on skills essential to good medical care by observing an actual clinical encounter. However, the bigger advantage of mini-CEX is the structured feedback that it provides to the students as well as the faculty, thus helping them to make better decisions. MATERIALS AND METHODS: This study was a cross-sectional observational study. Sixteen surgery residents volunteered for participation and five professors conducted sessions; hence, 80 mini-CEX encounters. Seven core clinical skill assessments were done, and the performance was rated on a 9-point scale (grouped into unsatisfactory, satisfactory, and superior). Immediate feedback to the residents was given by the faculty. Delayed feedback from faculty and residents regarding the perception of mini-CEX was taken. Statistical analysis was done using SPSS version 20 and analysis of variance (ANOVA) for inferential statistics. RESULTS: As planned, 80 (100%) mini-CEX encounters were conducted. Surgery residents showed improvement that was statistically significant in the competencies of medical interviewing skills, physical examination skills, humanistic qualities/professionalism, and counseling skills. Most of the faculty (80%) were able to identify the gaps in the knowledge of students and areas of improvement for their teaching. However, 60% of the faculty felt that it required more effort than traditional methods. The mean time taken by the assessor for observation and feedback to residents was 12.51 min and 5.68 min, respectively. The mean scores of evaluator satisfaction and resident satisfaction with mini-CEX sessions were 6.04 and 7.49, respectively. CONCLUSIONS: Mini-CEX improves the learning environment in residency and also leads to improvement in medical interviewing skills, physical examination skills, humanistic qualities/professionalism, and counseling skills. It is done in the actual patient encounter and hence prepares the resident better for dealing with patients in the future.